Understanding the characteristics of workforce transformation in a digital transformation context. (15th December 2022) - Alrasheedi, Naimah Saeed; Sammon, David; McCarthy, Stephen
ABSTRACT: Current literature has increased our knowledge of particular aspects of Workforce Transformation (WT), yet we need a comprehensive picture of its characteristics within a Digital Transformation (DT) context. Therefore, the objective of this review paper is to present the defining characteristics of WT. We fulfil this objective through a systematic review of 70 empirical papers published in leading journals listed on the CABS Academic Journal Guide (between 2010 and 2022). Following an inductive open coding approach, we identified six characteristics of WT: (1) 'Actors and Digital Competency'; (2) 'Digital Culture'; (3) 'Digitally Engaged Workspace'; (4) 'Empowerment, Engagement, and Motivation'; (5) 'Improvisation and Collaborative Visioning'; and (6) 'Transformational Leadership and Governance'. Based on these characteristics, we detail a future research agenda that proposes the need to examine the relationship between WT characteristics and DT outcomes.